Quantitative Precipitation Estimation from a C-Band Dual-Polarized Radar for the 8 July 2013 Flood in Toronto, Canada - Boodoo, Sudesh; Hudak, David; Ryzhkov, Alexander; Zhang, Pengfei; Donaldson, Norman; Sills, David; Reid, Janti (Journal of hydrometeorology, 2015)
A heavy rainfall event over a 2-h period on 8 July 2013 caused significant flash flooding in the city of Toronto and produced 126 mm of rain accumulation at a gauge located near the Toronto Pearson International Airport. This paper evaluates the quantitative precipitation estimates from the nearby King City C-band dual-polarized radar (WKR). Horizontal reflectivityZand differential reflectivityZ DRwere corrected for attenuation using a modified ZPHI rain profiling algorithm, and rain ratesRwere calculated fromR(Z) andR(Z,Z DR) algorithms. Specific differential phaseK DPwas used to compute rain rates from threeR(K DP) algorithms, one modified to use positive and negativeK DP, and anR(K DP,Z DR) algorithm. Additionally, specific attenuation at horizontal polarizationAwas used to calculate rates from theR(A) algorithm. High-temporal-resolution rain gauge data at 44 locations measured the surface rainfall every 5 min and produced total rainfall accumulations over the affected area. The nearby NEXRAD S-band dual-polarized radar at Buffalo, New York, provided rain-rate and storm accumulation estimates fromR(Z) and S-band dual-polarimetric algorithm. These two datasets were used as references to evaluate the C-band estimates. Significant radome attenuation at WKR overshadowed the attenuation correction techniques and resulted in poor rainfall estimates from theR(Z) andR(Z,Z DR) algorithms. Rainfall estimation from the Brandes et al.R(K DP) andR(A) algorithms were superior to the other methods, and the derived storm total accumulation gave biases of 2.1 and −6.1 mm, respectively, with correlations of 0.94. The C-band estimates from the Brandes et al.R(K DP) andR(A) algorithms were comparable to the NEXRAD S-band estimates.